Evoking of Spiritual Powers as Foundation for Inclusive Education - Martišauskienė, Elvyda (Pedagogika, 2014)
Inclusive education is based on the idea that all learners have to become participants in the process of (self-) education. This at first sight simple truth causes difficulties because of the variety of inborn human powers and in cases of learners with special needs, in particular. A wide range of strategies have been tested and applied for education of such children in Lithuania and all over the world. Lately significant attention has been laid on inclusive education. However, to achieve the desired outcomes, it is necessary to perceive methodological fundamentals and meaning of inclusive education to a teacher and a learner. Education is a specific activity, which is directed towards empowerment of an individual to spread own powers. Therefore, it is important to cognise the human nature and to derive the most significant approaches towards education from it. Contemporary science distinguishes three dimensions in the human nature, i.e., physical, psychical and spiritual ones, and their development is considered to be the main goal of a general education school. To enable appropriate attainment of this goal, it is necessary to perceive the essence of every dimension and their interrelation. The spiritual dimension causes the most serious concern. According to neurologist and psychotherapist V. Frankl, the genesis of the spiritual dimension is supernatural and enables an individual to transcendent the reality and to embody the existential freedom, whereof the real essence is revealed only through the interaction with truth (phenomenon of consciousness). An individual manages own physical and physical powers with the help of own spirit, is able to make decisions, to link own relations and activities with truth in an authentic way. The supreme expression of relations as well as that of spiritual dimension is love. The spiritual dimension is evoked and maturated by love of another individual, therefore, fruitful pedagogical support is always based on it. Moreover, V. Frankl points out that the spirit is never sick. Such approach to a human being enables us to understand why alpha and omega of education embrace spiritual powers of an individual, why teacher’s spiritual maturation becomes an important factor implementing the paradigm of free education, which contains inclusive education. It is of particular importance to learners with special needs because such education enables them to become full-value participants in the process of self-education in the most appropriate way to them, to experience success and to see the meaning of such activities. Healthy learners also feel advantages of inclusive education because it enables them to self-assess own potential and to envisage their real meaning in a new light. Inclusive education is relevant to teachers as a certain challenge to their spiritual as well as professional capacities, which reveals the in-depth essence of their activities.